Effect of graded erythrocythemia on cardiovascular and etabolic responses to exercise. - Spriet, L. L.; Gledhill, N.; Froese, A. B.; Wilkes, D. L. (Journal of Applied Physiology, 1986)
The effects of graded induced erythrocythemia on cardiovascular and metabolic responses to intense treadmill running were studied in four highly trained endurance runners. Three autologous infusions of 1 unit (U) whole blood (450 ml/U) were administered sequentially 2-7 days apart. Maximal O2 consumption (VO2max) increased from 5.04 l/min at control (C) to 5.24 l/min after 2 U (R2) and 5.38 l/min after 3 U (R3). Cardiac output during treadmill running at 91% control VO2max was 28.2 l/min at C, 29.8 l/min at R2, and 33.1 l/min at R3. Corresponding heart rates were unchanged, and stroke volume was increased at R3. Peak lactate concentration was reduced, and arterial acid-base status improved at R2 and R3 after standardized bouts of intense exercise. Arterial blood pressures and electrocardiograms during exercise were not affected by erythrocythemia. We conclude that the reinfusion of up to 3 U of autologous blood into highly trained endurance runners who have normal hematology does not adversely affect their cardiovascular response to maximal exercise. In addition, the increases in VO2max following reinfusion of 2 U, and again after 3 U, suggest that the aerobic power of the working muscles was not surpassed at these levels of erythrocythemia.